Planning and Layout Method for Community Bus Stops Based on Carbon Reduction Benefits - Yang LI; Chenyu XIANG; Ning LIU (Promet (Zagreb))
Regarding “carbon peaking and carbon neutrality goals”, with the transportation sector as a key area of carbon emissions, the development of low-carbon transportation is imminent. Urban bus route scheduling is pivotal in realizing carbon emission reduction in transportation, and this paper focuses on the achievement of optimal bus-stop layouts for increased convenience for residents. To realise carbon reduction benefits, this paper focuses on achieving the minimum personal bus trip average carbon emission, passenger trip costs and bus operation costs, while reducing the impact on other bus stops and routes by proposing bus stop planning and layout method under the micro-community scale. Through the simulated annealing algorithm, the optimised bus stop can optimise the average carbon emission of the residents’ personal trip by 36.87%, while the probability of residents choosing low-carbon trip increased by 4.94%, choosing medium-carbon trip increased by 1.48% and choosing high-carbon trip decreased by 10.84%, realising a substantial carbon reduction benefit. Furthermore, this paper introduces the emotional coefficient of the residents’ public transport trip to determine the effect of travel, waiting and connecting times thereof. Accordingly, new methods and ideas are presented for urban bus stop planning, and the process toward ‘carbon neutrality’ and ‘carbon peaking’ is accelerated.